PERAN MENANAMKAN TANGGUNG JAWAB ANAK USIA 5-6 TAHUN DI TK ISLAM AL-IKHWAH PONTIANAK KOTA - Nurhofifah, Nurhofifah; R, Marmawi; Amalia, Annisa (Universitas Tanjungpura, 2024)
This study aims to describe the teacher's role in cultivating the character of responsibility in children aged 5-6 years at the Islamic Kindergarten Al Ikhwah Pontianak City. The research method used is descriptive with a qualitative research form. The subjects in the study were class B1 teachers at the Al Ikhwah Islamic Kindergarten, Pontianak City. The research location is in the Al Ikhwah Islamic Kindergarten Pontianak City. Data collection techniques used in this study are observation, interviews, and documentation. The results of the study show that the teacher's role in cultivating the character of responsibility includes: 1. The role of the teacher as a guide in instilling the character of responsibility is to help, accompany, guide, and direct children who have difficulty in cultivating the character of responsibility. 2. The role of the teacher as a motivator in cultivating the character of responsibility is to provide motivation in the form of giving rewards (complimentary sentences or words of encouragement) to children so that they are moved to carry out activities related to the cultivation of the character of responsibility. 3. The role of the teacher as a facilitator in cultivating the character of responsibility is to provide learning facilities and tools to facilitate children in learning related to the cultivation of the character of responsibility.